2018
DOI: 10.1177/0725513618787638
|View full text |Cite
|
Sign up to set email alerts
|

Anti-politics, the early Marx and Gramsci’s ‘integral state’

Abstract: This paper traces a line of theorisation regarding the state-civil society relationship, from Marx's early writings to Gramsci's conception of the integral state. The paper argues that Marx developed, through his critique of Hegel, a valuable understanding of the state-civil society connection that emphasised the antagonism between them in capitalist societies. Alternatively, Gramsci's conception of the 'integral state' posits an interconnection and dialectical unity of the state and civil society, where the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…This article is also influenced by the Gramscian idea of the integral state, which sees continuities between political society and civil society (Gramsci 1999;Humphrys 2018). The concept of the integral state implies that coercion alone cannot guarantee state power but requires the construction of a consensus around a set of values (Thomas 2009).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…This article is also influenced by the Gramscian idea of the integral state, which sees continuities between political society and civil society (Gramsci 1999;Humphrys 2018). The concept of the integral state implies that coercion alone cannot guarantee state power but requires the construction of a consensus around a set of values (Thomas 2009).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Anti-politics, therefore, is not new, but in the current period can be seen as a ‘product of the breakdown of the political order that prevailed in many advanced capitalist countries for much of the last century’ (Humphrys, 2018: 41).…”
Section: Using Anti-politics As a Tool To Understand Responses To Thementioning
confidence: 99%
“…For individuals, the bureaucracy becomes an individual end, a situation which results in the state becoming a particular interest in itself (Marx, 1994). As Humphrys (2018: 32) argues:Marx identified that the antagonism between civil society and the state was unable to be resolved, precisely because in a society composed of competing particular interests, the state itself would be just another particular interest – even if in a formal or abstract way it claimed to stand for the general or collective interest of the society that it governed over.…”
Section: Using Anti-politics As a Tool To Understand Responses To Thementioning
confidence: 99%
See 2 more Smart Citations